Analisis Usability Testing pada User Interface dalam Game Idle Breeder - James James; Agung Riyadi (Politeknik Negeri Batam, 2021)
In today's development, children are used to using smart phones or smartphones. Most of these smartphones run on the Android or IOS operating system. In smartphones there are applications that can be used for various purposes. One type of these applications is games. In this case, there are still many users who play the game having difficulty understanding the layout and menus that have been presented in a game, making it difficult for users to play it. In this study the author will discuss the user experience in the game